EFEK SINERGIS ALUMINA TRIHYDRATE DAN MELAMINE CYANURATE TERHADAP SIFAT KUAT TARIK GLASS FIBER REINFORCED POLYMER - Ridha Inayah; Wiwik Dwi Pratiwi; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Glass Fiber Reinforced Polymer, commonly known as GFRP, is that as a train interior component, it must have good mechanical properties. The addition of flame retardant compounds contained in GFRP materials can affect the tensile strength of GFRP materials. In this study, GFRP composed of Alumina Trihydrate (ATH) and Melamine Cyanurate (MCA) powder was mixed into a vinyl ester resin. The method of making GFRP specimens uses the hand lay-up method. GFRP was mixed and tested for material with ASTM D-638 standard tensile test. The results obtained after the addition of 25% ATH, a mixture of 5%, 10%, and 15% MCA at 25% ATH, 25% ATH in the outermost layer, and a mixture of 5% MCA with 25% ATH in the outermost layer to the weight of the resin was a decrease in strength when the percentage of filler powder increases. Tensile strength, strain, and modulus of elasticity of GFRP were optimum at the addition of 25% ATH with 5% MCA to the weight of the resin in the outer layer. The result of tensile strength is 124.37 MPa, strain is 12.76%, and modulus of elasticity is 975.85 MPa. The results show that a mixture of ATH and MCA has a synergistic effect, so that it becomes a recommendation for interior sidewall panels and ceiling panels on trains.